HEMOGLOBIN SCREENING EXAMINATION IN ADOLESCENTS AT SMK PGRI 2 TUBAN AS EARLY DETECTION OF ANEMIA - Lilik Khoufah; Eko Winarti (Suluh Adiluhung Publisher (SAPub), 2025)
Anemia in adolescents is a serious public health problem because adolescence is an important developmental period in the life of every individual, where adolescence is experiencing biological, psychological and behavioral changes that affect their health. Factors that contribute to the incidence of anemia in adolescents include lack of iron intake in food, unbalanced diet, the habit of skipping breakfast, and lack of awareness of the importance of clean and healthy living behavior. Anemia is diagnosed with the examination of hemoglobin (Hb) in the blood. It is said to have Mild Anemia if Hb is 11 - 11.9 gr / dl, Moderate Anemia if Hb is 8 - 10.9 gr / dl and Severe Anemia if Hb <8 gr / dl. This anemia screening is carried out by examining Hemoglobin levels with the POCT method. The results of the screening carried out at SMK PGRI 2 Tuban, East Java, which were carried out on 70 female students showed that 4 (5.71%) female students were detected as having anemia.